Deception and self-deception in health care - de Vries, Jan M. A. (Nursing philosophy, 2016)
Deception is part of the natural repertoire of adaptive behaviours in many organisms. In humans we see it in all domains of human activity including health care. Within health care, deception can be a matter of concern, but it is also used to protect patients, for instance against overwhelming and negative diagnostics. This paper demonstrates that deception and self-deception are closely interlinked and that self-deception facilitates deception. Furthermore, self-deception tends to be used to reduce the discomfort we feel when we are dishonest (cognitive dissonance). The paper includes references to core psychological mechanisms and ethical aspects.